Lymphocytic interstitial non-HIV-related pneumonia in pediatrics: a case report - Murillo Casas, Andrea Dionelly; Duarte Dorado, Diana María; Olaya Hernández, Manuela (Frontiers in Pediatrics, 2024)
Lymphocytic interstitial pneumonia (LIP) in pediatric patients without human immunodeficiency virus (HIV) infection remains a poorly characterized and enigmatic disease. Immunological dysregulation, This is a provisional file, not the final typeset article mutations in the COPA gene, and increased morbidity and mortality have been reported in these patients. We present a case of LIP in a pediatric patient without HIV infection. This patient was infected with human T-lymphotropic virus type 1 (HTLV-1) and required right lower lobectomy with pathological findings compatible with lymphocytic interstitial pneumonia. In addition, bronchiectasis, dermatological involvement, and malnutrition were documented. However, no autoimmune disease, polymyositis, myelopathy, or opportunistic infections were found. There were no abnormalities in cellular and humoral immunity. A genetic study identified heterozygous mutations in the SCNN1B, FCHO1, and IL7R genes using single exome sequencing of coding and splicing regions. Although these heterozygous variants are not reported to be aetiological for LIP or diagnostic for the patient's congenital immunodeficiency, we believe they are associated with the severe lung damage seen in the patient's case.